Draft report on hospital administration from the point of view of the patient : to be presented at the National Conference of Labour Women at Blackpool
1931-06 1931 1930s 5 pages - 5 - But even this inhuman argument does not fit the circumstances of today, since charges are often made. In our view there is no reason why a time-table for patients should not be drawn up so that waiting can be reduced to a reasonable minimum for each patient. In America it is the custom to have an office attached to the hospital where appointments are made for the out-patient department. This system has been tried with great success in a Manchester Hospital. B. Accommodation. Accommodation for waiting is especially important if the period is to be a long one. Today the cheerless discomfort is often such as to reduce patients to a pitiful state of nervous exhaustion. In some cases persons with skin diseases or some other complaint of an unpleasant or even infectious character are packed closely together for a long wait and sights and sounds of an unnerving character are a bad introduction to an interview with the doctor. There should always be a rest room apart from the general waiting room for use after seeing the doctor. C. Buffet. Simple food such as milk, tea, biscuits and bread and butter should be procurable at low charges. CONCLUSION. We desire to draw the attention of the public to these needs of patients. It is clear that we require more hospital beds, more nurses, less overworked nurses, better equipment and service and better provision for the patients' wellbeing whether as an in-patient or an out-patient. The existence of isolated hospital units as we have now under the voluntary system is not and cannot be for the public good. Only a co-ordinated system can give full service. The voluntary hospitals have long been conducted with special attention to the convenience of its honorary staff of doctors rather than to the comfort of patients. Since the Voluntary Hospitals cannot provide what is necessary it is urgent to establish a system of hospital accommodation under public control and paid for from public funds. We must do our best to see that all hospitals now under the Public Health Authorities give full attention to those needs which we have described. But we must not be content until there is a complete scheme which will give to every patient the fullest opportunity of speedy and complete recovery. 292/842/1/8